CLINICAL TESTS OF PHYTOPREPARATE IN COMPLEX THERAPY OF ACUTE RESPIRATORY DISEASES - Вековцев, Андрей Алексеевич; Позднякова, Ольга Георгиевна; Белавина, Галина Андреевна; Позняковский, Валерий Михайлович (Medicine in Kuzbass, 2019)
The aim of the study – the clinical approbation of a new phytocomplex in the complex therapy of acute respiratory diseases. Materials and methods. Thirty patients with acute respiratory diseases were examined, whose diet, during 28 days, included a specialized product in the form of a phytocomplex of 1 capsule 2 times a day. Clinical trials were carried out on the basis of the city hospital N 3 (Tomsk). Results. The parameters of changes in clinical symptoms of the disease, hematological tests, subpopulation composition of peripheral blood lymphocytes, serum IFN-γ content indicate activation of the antiviral response of immunocompetent cells, reduction of the inflammatory process, acceleration of the processes of relief of the general intoxication syndrome, which as a whole makes it possible to shorten the duration of the disease. The conclusion. Clinical evidence of the effectiveness of the tested form of biologically active additive with the presence of anti-inflammatory and immunomodulating effect was obtained. Phytopreparation can be recommended in the complex therapy of acute respiratory diseases and the prevention of their occurrence.